Socio-Clinical Correlations With Threat Perception and Self-Efficacy in People With Type 2 Diabetes. - Hu, Jianli; Bass, Sarah Bauerle; Swavely, Deborah; Zisman-Ilani, Yaara; Chen, Sophia K.; Kim, Sarah; Kelly, Patrick J.A.; Hoadley, Ariel; Rubin, Daniel J. (Diabetes Spectrum)
The article focuses on the prevalence and management of type 2 diabetes, particularly among medically underserved populations, and explores the application of the Extended Parallel Processing Model (EPPM) to categorize individuals based on their perceptions of threat and self-efficacy. The study involved 168 adults with type 2 diabetes from urban safety-net clinics, revealing significant differences in medication adherence, self-management behaviors, and diabetes-related complications across four EPPM categories. Findings suggest that individuals with lower self-efficacy and higher perceived threat may benefit from tailored interventions to improve diabetes management. The study highlights the potential for using the EPPM framework to enhance patient outcomes through personalized strategies.